Kajian Konsep Arsitektur Modern pada Bangunan Surabaya Kriya Gallery Merr - Nafisah, Durotun; Rolalisasi, Andarita; Faisal, Muhammad (SADE : Jurnal Arsitektur, Planologi dan Teknik Sipil, 2024)
UMKM (Usaha Mikro, Kecil dan Menengah) have an important role in regional and national economic growth. Every year the number of UMKM always increases in each region, one of which is Surabaya City. With the large number of UMKM, facilities are needed that can develop this, one of the Surabaya City Government's strategies to develop UMKM products in Surabaya City is by providing facilities to UMKM players in the form of a forum to market their products and also coaching to develop the products of UMKM players.